Implementasi User Accepted Test pada Pengujian Sistem Informasi Daerah Rawan Kriminalitas - Hartono, Nahrun; Muin, Asrul Azhari; Passolongi, Haykal (Journal Software, Hardware and Information Technology, 2023)
Data collecting and mapping of criminal data have been carried out for a long time by recording criminal acts on paper (books). Otherwise, collecting data uses office applications, while mapping is done by marking on the map. The goal is to find out the highest crime rate in an area. The mapping results are a reference for the authorities to improve surveillance and education in areas with high crime rates. This method has many drawbacks, including the possibility of data being overwritten. System testing uses black box testing, while feasibility Testing uses the User Accepted Test (UAT) method. User Accepted Test testing is done by asking respondents to use the system and then giving responses to the questions given. Ten questions were asked with an assessment score using a Likert scale. After that, search for the percent value for each question to get the average score. The average score is the final result of the User Accepted Test. The results of this study are an average score of 89.88%. Based on the User Accepted Test score criteria, the average respondent strongly agrees with the developed application.